Effects and mechanisms of acupuncture for PIGD-subtype Parkinson’s disease via integration of fMRI and gut microbiota-metabolomics analysis: protocol for a prospective randomized controlled trial - Jili Sheng; Jili Sheng; Yingqi Xu; Tao Liu; Jianfang Zhu; Caiyun Mu; Lihao Zhai; Shanhu Xu; Hanyi Wang; Xiangzhi Liu; Tao Liu; Xiaoqing Jin (Frontiers in Aging Neuroscience)
IntroductionParkinson’s disease (PD) can be categorized into various subtypes based on the primary symptoms associated with motor dysfunction. One subtype, known as postural instability and gait difficulty (PIGD), is characterized by severe clinical symptoms, an increased risk of walking difficulties and falls, and a poorer prognosis compared to other subtypes. This condition imposes a significant burden on patients, their families, and the healthcare system. Recently, acupuncture, a practice rooted in traditional Chinese medicine, has gained attention for its potential to influence neurophysiological pathways and enhance the overall brain function in individuals with PD. This randomized controlled study aimed to evaluate the clinical effectiveness of acupuncture in patients with the PIGD subtype of PD and to investigate the preliminary exploration of mechanisms of acupuncture by analyzing intestinal microbiota and metabolomics, thereby providing deeper insights into its impact on patients.MethodsThis randomized controlled trial will involve 64 patients diagnosed with the PIGD subtype of PD. Participants in both groups will undergo three acupuncture sessions weekly for a duration of 4 weeks, followed by an 8-week follow-up period. The primary outcome measure will be the Unified Parkinson’s Disease Rating Scale III. Secondary outcomes will include the Berg Balance Scale (BBS), wearable gait analysis, and functional magnetic resonance imaging (fMRI). Additionally, serum and stool samples will be collected for 16S ribosomal RNA sequencing, and liquid chromatography coupled with tandem mass spectrometry analysis (LC–MS/MS) will be employed to elucidate theunderlying mechanisms. This trial has been reviewed and approved by the Medical Ethics Committee of Zhejiang Hospital (Approval no. 2023-15 K). Participation in this study will require written informed consent from all patients. The findings of this study will be published in a peer-reviewed journal, and there will be no restrictions on publication.DiscussionIn this study, we integrate traditional assessment scales with fMRI to demonstrate the therapeutic effects of acupuncture. We will also analyze the modulation of gut microbiota and serum metabolome to explore the underlying neural mechanisms. Our results will provide a foundation for future studies in this area.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR2300071703.